Cryotherapy as a non-pharmacological alternative for the management of postoperative endodontic pain: An integrative review of the literature (Research, Society and Development, 2021)
Introduction: Pain management is one of the main objectives within dental practice and is one of the most common reasons for patients to seek dental care, it is generally associated with trauma and infections that require endodontic treatment, whose purpose is to preserve the affected tooth, eliminate inflammation and prevent infection; however, it also implies the appearance of postoperative pain that could vary from 1.5% to 53%. Materials and Methods: The present study is an integrative review of the literature in which the existing scientific evidence about cryotherapy as a non-pharmacological alternative for the management of post-endodontic pain was analyzed. To do this, an exhaustive search of the pertinent information was carried out in the Science Direct, Medline, Cochrane, PubMed databases, as well as a manual search, of articles since 2014. Results: The search carried out yielded 112 articles, of which 22 were selected, which were adjusted with the objectives and inclusion criteria of the research. Those that did not contain the keywords in the title and / or abstract were excluded. Conclusions: Current scientific evidence supports the use of cryotherapy as an inexpensive and effective non-pharmacological alternative for the control of inflammation and post-endodontic pain, so it could be considered a valid option for its routine clinical application.